Acquirement of Writing System as Plot of Spiritual Culture of the Adyghe and Personality of L. G. Afashagov - I. A. Kazharova (Научный диалог)
The study presents aspects of creative activities and biography of Adyghe poet and essayist of the early Soviet period Lostanbe Guruzhevich Afashagov. The problems that become the subject of consideration in modern studies on the history of the Adyghe literature are identified. Reflected in the history of the formation of the national writing system of the Adyghe the milestones of spiritual search and spiritual transformation of the ethnic group and their gradual transformation into a plot of artistic reflection are reviewed, motif of dramatic confrontation, which became part of this plot, is actualized. L. G. Afashagov’s educational and journalistic work is covered. According to the materials of newspaper publications and archival evidence, the stages of his active participation in the history of preparing for the publication of the first novel in Kabardian literature are restored. The author analyzes in detail one of his poetic works in relation to the context of the formation of the national writing system of the Adyghe, the most active stage of which falls on the first decades of the 20th century. The reasons why the name of one of the representatives of the Adyghe intelligentsia of the 1930s was in complete oblivion are considered. The novelty of the research is that the name and work of L. G. Afashagov are introduced into scientific circulation for the first time.